2010
DOI: 10.1093/humrep/deq138
|View full text |Cite
|
Sign up to set email alerts
|

Speriolin is a novel human and mouse sperm centrosome protein

Abstract: Speriolin is a novel centrosomal protein present in the connecting piece region of mouse and human sperm that is transmitted to the mouse zygote and can be detected throughout the first mitotic division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 71 publications
4
32
0
Order By: Relevance
“…Late transcribed retained sperm transcripts encode proteins like IZUMO1 (Chalbi et al 2014) that are essential for fertilization. They also encode proteins required for early embryogenesis, e.g., centrosomal proteins, e.g., SPATC1, a sperm protein that is delivered to the oocyte and maintained after the first division (Goto et al 2010). This corresponding selective retention of sperm RNAs encoding proteins in conjunction with some of their products that are essential for fertilization and early embryogenesis is consistent with the view that their late transcription and translation in the differentiating spermatid acts to ensure their availability prior to zygotic genome activation.…”
Section: Transcripts Versus Proteinsmentioning
confidence: 99%
“…Late transcribed retained sperm transcripts encode proteins like IZUMO1 (Chalbi et al 2014) that are essential for fertilization. They also encode proteins required for early embryogenesis, e.g., centrosomal proteins, e.g., SPATC1, a sperm protein that is delivered to the oocyte and maintained after the first division (Goto et al 2010). This corresponding selective retention of sperm RNAs encoding proteins in conjunction with some of their products that are essential for fertilization and early embryogenesis is consistent with the view that their late transcription and translation in the differentiating spermatid acts to ensure their availability prior to zygotic genome activation.…”
Section: Transcripts Versus Proteinsmentioning
confidence: 99%
“…SPATC1L-This speriolin-like protein is of unknown function, whereas speriolin is a spermatogenic cell-specific centrosomal protein (50). Before activation, CFP-SPATC1L was distributed in the cytoplasm, the nucleus and in the perinuclear region.…”
Section: Identification Of Fluorescently Labeled Proteins That Responmentioning
confidence: 99%
“…Other proteins in the mature sperm are only incompletely understood although new studies have started to focus on this topic. Recently, Goto et al (2010) reported that speriolin is present in sperm of human and mouse oocytes and is contributed to the oocyte after fertilization; it is detected at the mitotic poles in both systems despite the fact that in the mouse, the sperm centriole is destroyed and does not participate in the fertilization process (Schatten et al 1985a). One complexity regarding sperm centrosomal components relates to the fact that many previous studies have used immunofluorescence microscopy without extensive control experiments to possibly unmask antigens that may not be detected because of inaccessibility to the antibody.…”
Section: Introductionmentioning
confidence: 99%